Identification of novel multitargeted PPARα/γ/δ pan agonists by core hopping of rosiglitazone - Wang XJ; Zhang J; Wang SQ; Xu WR; Cheng XC; Wang RL (Dove Medical Press, 2014)
Xue-Jiao Wang,1 Jun Zhang,1 Shu-Qing Wang,1 Wei-Ren Xu,2 Xian-Chao Cheng,1 Run-Ling Wang1 1Tianjin Key Laboratory on Technologies Enabling Development of Clinical Therapeutics and Diagnostics (Theranostics), School of Pharmacy, Tianjin Medical University, Tianjin, People’s Republic of China; 2Tianjin Key Laboratory of Molecular Design and Drug Discovery, Tianjin Institute of Pharmaceutical Research, Tianjin, People’s Republic of China Abstract: The thiazolidinedione class peroxisome proliferator-activated receptor gamma (PPARγ) agonists are restricted in clinical use as antidiabetic agents because of side effects such as edema, weight gain, and heart failure. The single and selective agonism of PPARγ is the main cause of these side effects. Multitargeted PPARα/γ/δ pan agonist development is the hot topic in the antidiabetic drug research field. In order to identify PPARα/γ/δ pan agonists, a compound database was established by core hopping of rosiglitazone, which was then docked into a PPARα/γ/δ active site to screen out a number of candidate compounds with a higher docking score and better interaction with the active site. Further, absorption, distribution, metabolism, excretion, and toxicity prediction was done to give eight compounds. Molecular dynamics simulation of the representative Cpd#1 showed more favorable binding conformation for PPARs receptor than the original ligand. Cpd#1 could act as a PPARα/γ/δ pan agonist for novel antidiabetic drug research. Keywords: PPARs, diabetes, docking, molecular dynamics simulation, ADMET